Energy Trading in Prosumer based Smart Grid Integrated with Distributed Energy Resources - Boddapati, Krishna Mohan; Patne, Nita R.; Manchalwar, Ashwini D. (2022 International Conference on Intelligent Controller and Computing for Smart Power (ICICCSP), 2022)
Energy trading in a smart microgrid based Peer to Peer (P2P) microgrid requires a novel framework. Where in a microgrid each prosumer equipped with Distributed Energy Resources (DER) is encouraged to trade energy. Energy is traded with peers in the microgrid or sold to power grid to generate revenue whenever there is a surplus of energy. As there is an economic benefit, more prosumers are attracted to install DER. The peers in the microgrid are incentivized to buy locally produced energy which is available at a cheaper cost compared to buying from power grid. This results in reducing energy consumption from power grid which in turn results in reducing power losses in transmission lines and results in reduction of CO_{2} emissions. Three market paradigms are considered in this paper, i.e. Bill sharing, Supply to Demand Ratio method and Mid-market rate method. Each of the pricing models are elaborated with local energy trading price and prosumers energy costs. In this case, these methods are studied concerning a smart microgrid equipped with DER, Solar Photovoltaic (SPV) system in this case, and the effectiveness of the pricing mechanisms and their respective benefits are established.